2021
DOI: 10.3897/phytokeys.176.58825
|View full text |Cite
|
Sign up to set email alerts
|

Impatiens wutaishanensis (Balsaminaceae), a new species from Southeast Yunnan, China

Abstract: Impatiens wutaishanensis R.L. Liao & Lei Cai, a new species from Southeast Yunnan, China, is here described and illustrated. This new species is most similar to Impatiens parvisepala S.X. Yu & Y.T. Hou in its racemose inflorescences, its four lateral sepals, the leaf arrangement, and in having yellow flowers. However, it differs in the height of the plants, the length of the petiole, the size and shape of the leaf blade, the shape of the spur, and the number of flowers in each inflorescence. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,334 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Specimens were collected, preserved, and deposited in the Herbarium of Wuhan Botanical Garden, Chinese Academy of Sciences (HIB) for further identification. We then dissected the flower and carefully reviewed related literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]36,37] and herbaria specimens in a bid to ascertain the identity of the collected species. However, we were unable to match the new plants with any described species based on morphology.…”
Section: Identification and Description Of New Taxonmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimens were collected, preserved, and deposited in the Herbarium of Wuhan Botanical Garden, Chinese Academy of Sciences (HIB) for further identification. We then dissected the flower and carefully reviewed related literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]36,37] and herbaria specimens in a bid to ascertain the identity of the collected species. However, we were unable to match the new plants with any described species based on morphology.…”
Section: Identification and Description Of New Taxonmentioning
confidence: 99%
“…The Flora of China lists 227 species, of which 187 are endemic [14]. According to Du et al [15], a total of 69 new taxa of Impatiens have been described in China between 2000 and 2019, and 13 new taxa [16][17][18][19][20][21][22][23][24][25][26][27][28] and three new records [28][29][30] have been published in the last two years, bringing the total species reported for China to nearly 290.…”
Section: Introductionmentioning
confidence: 99%
“…In China, 349 species of Impatiens have been recorded ( Yuan et al in press ), the overwhelming majority of them being distributed in the southwest region, including Yunnan, Sichuan, Tibet and Guizhou ( Chen 2001 ; Yu 2012 ). Since 2021, according to our incomplete statistics, eight new species of Impatiens have been described from China ( Gu et al 2021 ; Liao et al 2021 ; Peng et al 2021a , b ; Song et al 2021a , b , c ). In Guizhou, 61 species of Impatiens have been recorded ( Peng et al 2021a ; Yu et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Impatiens Linnaeus (1753 : 937), belonging to the Balsaminaceae , consists of more than 1000 species, mainly distributed in the montane forests of the tropics and subtropics of the Old World with five centres of diversity, namely tropical Africa, Madagascar, south India and Sri Lanka, eastern Himalaya and Southeast Asia ( Grey-Wilson 1980 ; Song et al 2003 ; Yuan et al 2004 ; Mabberley 2017 ). In recent years, a few new species have also been found in the northern temperate regions of Europe, Russia and China, as well as North America ( Liao et al 2021 ). Currently, there are more than 349 species of Impatiens in China ( Yuan et al, in press ) which are distributed mainly in the southwest and northwest mountainous regions, especially in southwest Provinces (including Guizhou, Yunnan, Sichuan) ( Chen 2001 ; Chen et al 2007 ; Cai et al 2015 ; Kuang 2015 ; Tan et al 2015 ; Ding et al 2016 , 2017 ; Xia et al 2019 ; Gu et al 2021 ; Liao et al 2021 ; Peng et al 2021b ; Song et al 2021a , b , c ) and 61 species of Impatiens have been reported in Guizhou Province ( Xiong and Yang 2009 ; Cong 2010 ; Kuang et al 2014 ; Luo and Deng 2015 ; Peng et al 2021a ; Yu et al 2021 ; Yuan et al in press ).…”
Section: Introductionmentioning
confidence: 99%